The Impact of Marketing Communication Tools towards Brand Awareness of Restaurant X in ABC Hotel - Jasman, Ivana Christina (iBuss Management, 2015)
Nowadays, the tourism industry is highly competitive. Many hotels compete with each other and try to distinguish themselves by building restaurants as their facilities. It is importantÂ  for them to build the brand awareness because it will give impact on consumersâ choice inÂ  buying decision. Taking the case of Restaurant X in ABC Hotel, this research will answer whether the marketing communication mix simultaneously and significantly gives influence towards brand awareness. The marketing communication toolsÂ  consists of advertising, sales promotion, public relation, and direct marketing.Â This research is based on the questionnaires that were distributed based on convenience sampling method to 93 correspondents who know Restaurant X. Using multiple regression, data are regressed based on the marketing communication mix performance and the brand awareness of Restaurant X. It shows that the marketing communication tools indeed simultaneously give significant influence towards brand awareness of Restaurant X. In addition, only sales promotion and public relation that individually give significant influence towards brand awareness of Restaurant X. Therefore, the management should intensify their strategy in monetary sales promotion and improve the sales promotion byÂ  adding non-monetary sales promotion, improve the public relation in online channels, and build integrated marketing communication for Restaurant X. Keywords: advertising, sales promotion, public relation, direct marketing, marketing communication tools, brand awareness.